Reducing Potentially Preventable Dental Hospitalizations of Young Children: A Community-Level Analysis. (July 2018) - Rogers, J.G.; Adams, G.G.; Wright, F.A.C.; Roberts-Thomson, K.; Morgan, M.V.
An increasing number of Australians are being admitted to hospitals and day procedure centers to have dental treatment under a dental general anesthetic (DGA). Children younger than 2 y are having DGAs. These operations are costly and, although there have been improvements in safety, are not without risk. Most DGAs in children are to treat dental caries and have been defined as potentially preventable dental hospitalizations (PPDHs). This article reports on an analysis of the impact of access to community water fluoridation (CWF), availability of oral health professionals (OHPs), and socioeconomic status (SES) on PPDHs of 0- to 4-y-olds in 2012–2013 in Victoria, Australia. Data on these variables were obtained at the community (postcode) level. From the negative binomial multivariate analysis, each of the 3 independent variables was independently significantly associated with PPDHs at the postcode level. Children residing in postcodes without CWF on average had 59% higher rates than those with access (incident rate ratio [IRR], 1.59; P < 0.0001), children in postcodes with the lowest level of availability of OHPs had 65% higher rates than those with the highest access (IRR, 1.65; P < 0.0001), and children living in the most disadvantaged SES quintiles had 57% higher rates than children in the most advantaged quintiles (IRR, 1.57; P < 0.0001). There was a stepwise social gradient by SES quintile. In analysis of access to CWF and SES status, children without access to CWF had 86% higher PPDH rates than children with access (IRR, 1.86; P < 0.0001). In summary, no access to CWF, poor availability of OHPs, and lower SES status were independently associated with higher PPDH rates among 0- to 4-y-olds in Victoria at the postcode level. The study highlights the importance of considering 3 interacting factors—access to CWF, access to OHPs, and SES—in efforts to reduce PPDH rates in young children. Knowledge Transfer Statement: Extending access to water fluoridation, increasing the availability of dental services, and raising disadvantaged families' socioeconomic status are each likely to decrease the rate of dental general anesthetics in young children.